Organic anion transporting polypeptides OATP1B1 and OATP1B3 and their genetic variants influence the pharmacokinetics and pharmacodynamics of raloxifene - Trdan Lušin Tina (Journal of Translational Medicine, 2012)
Abstract Background Raloxifene, a selective estrogen receptor modulator, exhibits quite large and unexplained interindividual variability in pharmacokinetics and pharmacodynamics. The aim of this study was to determine the role of organic-anion transporting polypeptides OATP1B1 and OATP1B3 and their genetic variants in the pharmacokinetics and pharmacodynamics of raloxifene. Methods To test the role of OATP1B1 and OATP1B3 transporters on hepatic uptake of raloxifene and its metabolites an in vitro model of Chinese Hamster Ovary cells expressing OATP1B1 or OATP1B3 was employed. The influence of OATP1B1 and OATP1B3 genetic variants on in vivo pharmacokinetics and pharmacodynamics was evaluated in 53 osteoporotic postmenopausal women treated with raloxifene. Results Our in vitro results showed that raloxifene and two of the three metabolites, raloxifene-4'-β-glucuronide (M2) and raloxifene-6,4'-diglucuronide (M3), interact with OATP1B1 and OATP1B3. Higher M3 and total raloxifene serum concentrations in patients correlated with lower serum levels of bone resorption marker, serum C-terminal telopeptide fragments of type I collagen, indicating a higher antiresorptive effect of raloxifene. Higher concentrations of M2 correlated with higher increase of lumbar spine bone mineral density supporting the raloxifene vertebral fracture specific protection effect. Finally, raloxifene, M3 and total raloxifene serum concentrations were significantly higher in patients with SLCO1B1 c.388A > G polymorphism and *1b haplotype implicating a considerable genetic effect on pharmacokinetics and pharmacodynamics of raloxifene. Conclusions These findings indicate that SLCO1B1 c.388A > G polymorphism could play an important role in pharmacokinetics and pharmacodynamics of raloxifene.